Optimizing Barium Titanate Nanocomposite Bone Scaffolds for Biomineralization in Dynamic Compression Bioreactors Using Time-Lapsed Microstructural Imaging and Smart Thresholding - Schädli, Gian Nutal; David, Helena; de Leeuw, Anke M.; Carlson, Franklin; Tenisch, Lara; Muff, Pascal; Rubert, Marina; Müller, Ralph (Frontiers in Materials, 2022)
Bone scaffolds made of calcium phosphate polymer nanocomposites have limited osteoinductive properties. Piezoelectric materials have attracted considerable interest in bone tissue engineering due to their potential to promote osteogenesis through additional electrical stimulation. Time-lapsed micro-CT imaging is a time-effective tool for in vitro optimization of such scaffolds but is challenged by nanocomposites with a high attenuation coefficient, such as one containing high amounts of piezoelectric barium titanate. We used high-resolution end-point micro-CT scans combined with histology and Raman spectroscopy to screen polydopamine functionalized nanocomposites containing 3–27 vol% barium titanate for collagenous extracellular matrix formation and mineralization. All compositions showed well-connected extracellular matrix and birefringent matured collagen after seven weeks of static human mesenchymal stem cell cultures. Nevertheless, high-resolution micro-CT analysis combined with smart thresholding during image processing enabled us to observe modest differences in ECM mineralization between groups suggesting that a volume fraction of 9–21% barium titanate facilitated the formation of dense mineral clusters in the pores even in the absence of mechanical stimuli, further corroborated by Raman spectroscopy. The same image processing approach facilitated the analysis of time-lapsed micro-CT images of scaffold cultures in dynamic compression bioreactors where 9 vol% barium titanate was the best nanocomposite composition, resulting in a significant twofold increased maturation rate under dynamic conditions. On the other hand, barium titanate content of ≥15 vol% did not improve mineralization. At 27 vol%, the biomineralization of the collagenous extracellular matrix was even impeded in the nanocomposite scaffolds, as evidenced by histology stainings. Overall, our approach enables time-lapsed quantitative assessment of high X-ray absorbing nanocomposite scaffolds for biomineralization under dynamic compression, facilitating the optimization of such mechanically responsive scaffolds.